Asuhan Keperawatan Keluarga pada Tahap Perkembangan Dewasa Muda Dengan Intervensi Pemberian Jus Nanas dan Madu untuk Menurunkan Kadar Asam Urat (Gout Arthritis) - Tsani Dermawan; Alfika Safitri; Hasan Basri (Jurnal Ventilator, 2024)
Gouty arthritis or often known as gout is a disease that attacks the joints, this is caused by high uric acid levels caused by genetic or hereditary factors and a lifestyle that often consumes foods that contain lots of purines. Purine substances are the core part of protein, and protein is widely obtained in offal foods, meat and beans (Uric Acid, 2023). Complementary therapy is a natural therapy including herbal therapy. Herbal therapy can utilize surrounding fruits / plants such as pineapple fruit, soursop fruit, bay leaves, and soursop leaves. This research uses a case study method with a family nursing care approach with gout. data collection instruments use family nursing care assessment formats through the nursing process of assessment, diagnosis, intervention, implementation, evaluation. Based on the results of the study after implementation in the patient, the results showed a decrease in the pain scale and an increase in the patient’s sense of comfort. Non-pharmacological pain management carried out is by drinking pineapple juice and honey regularly. Evaluation results found after treatment for 3 days with reduced pain data, pain scale 1-2. The evaluation found after treatment for 3 days of ineffective family health management problems related to the family’s inability to care for sick family members with family data can understand about gout and its actions.